Palmitate inhibits arthritis by inducing t-bet and gata-3 mRNA degradation in iNKT cells via IRE1α-dependent decay. Issue 1 (December 2017) - Ko, Jae; Koh, Jae; So, Jae-Seon; Jeon, Yoon; Kim, Hye; Chung, Doo
Abstract Long chain fatty acids (LCFAs) exert pro-inflammatory effectsin vivo . However, little is known regarding the effect of LCFAs on invariant (i ) NKT cell functions. Here, we report an inhibitory effect of saturated LCFAs on transcription factors ini NKT cells. Among the saturated LCFAs, palmitic acid (PA) specifically inhibited IL-4 and IFN-γ production and reducedgata-3 andt-bet transcript levels ini NKT cells during TCR-mediated activation. Ini NKT cells, PA was localized and induced dilation in the endoplasmic reticulum and increased the mRNA levels of downstream molecules of IRE1α RNase. Moreover, PA increased the degradation rates ofgata-3 andt-bet mRNA, which was restored by IRE1α inhibition or transfection with mutantgata-3 ort-bet, indicating thatgata-3 andt-bet are cleaved via regulated IRE1α-dependent decay (RIDD). A PA-rich diet and PA injection suppressed IL-4 and IFN-γ production byi NKT cells in C57BL/6, but not Jα18 knockout mice, which was restored by injection of STF083010, an IRE1α-specific inhibitor. Furthermore, a PA-rich diet and PA injection attenuated arthritis in ani NKT cell-dependent manner. Taken together, our experiments demonstrate that a saturated LCFA induced RIDD-mediatedt-bet andgata-3 mRNA degradation ini NKT cells, thereby suppressing arthritis.